Fecal carriage and molecular epidemiology of mcr-1-harboring Escherichia coli from children in southern China - Jialiang Mai; Zhuwei Liang; Zhile Xiong; Chao Zhang; Hao Cai; Shuwen Yao; Xiantang Chen; Bingshao Liang; Fei Gao; Zhuohong Huang; Fangjun Lan; Shuyan Liu; et al. (Elsevier, 2023)
Background: The increase of multidrug-resistant Enterobacteriaceae bacteria has led to the reintroduction of colistin for clinical treatments, and colistin has become a last resort for infections caused by multidrug-resistant bacteria. Enterobacteriaceae bacteria carrying the mcr-1 gene are majorly related to colistin resistance, which may be the main reason for the continued increase in the colistin resistance rate of Enterobacteriaceae. The study aimed to investigate the sequence type and prevalence of Escherichia coli (E. coli) harboring the mcr-1 gene in the gut flora of children in southern China. Methods: Fecal samples (n = 2632) of children from three medical centers in Guangzhou were cultured for E. coli. The mcr-1-harboring isolates were screened via polymerase chain reaction (PCR). The colistin resistance transfer frequency was studied by conjugation experiments. DNA sequencing data of seven housekeeping genes were used for multi-locus sequence typing analysis (MLST). Results: PCR indicated that 21 of the 2632 E. coli (0.80%) isolates were positive for mcr-1; these strains were resistant to colistin. Conjugation experiments indicated that 18 mcr-1-harboring isolates could transfer colistin resistance phenotypes to E. coli J53. MLST analysis revealed that the 21 isolates were divided into 18 sequence types (STs); E. coli ST69 was the most common (14.3%), followed by E. coli ST58 (9.5%). Conclusion: These results demonstrate the colonization dynamics and molecular epidemiology of E. coli harboring mcr-1 in the gut flora of children in southern China. The mcr-1 gene can be horizontally transmitted within species; hence, it is necessary to monitor bacteria that harbor mcr-1 in children.